Factors Related to Acute Respiratory Infection Among Toddlers - Novelia, Shinta; Rukmaini, Rukmaini; Kartika, Maudy Lila; Shrestha, Amrita; Durimalang, Sanches Evi (International Health Sciences Journal, 2023)
Background: Acute Respiratory Infection (ARI) is the main cause of child morbidity and mortality in the world. ISPA disease is the first most common disease experienced by the group of toddlers at the Menteng District Health Center at the MTBS poly. Objective: to determine the factors associated with the incidence of ARI in toddlers at the Menteng District Health Center, Central Jakarta in 2017. Methodology: This type of research is an analytic survey with a cross-sectional design. The population in this study were all mothers of toddlers who visited the MTBS polyclinic at the Menteng District Health Center with a total sample of 83 respondents who were taken by accidental sampling technique. Data collection was carried out using a questionnaire, observation of KMS (Health Card) and medical records. Univariate and bivariate data analysis using the chi square statistical test with a confidence level of 95% (α = 0.05). Results: The study showed that there was a relationship between nutritional status (p=0.030) and mother's knowledge (p-value 0.021) with the incidence of ARI in toddlers. Meanwhile, the variables of immunization status (p=0.120), exclusive breastfeeding (p=1) and mother's education (p=0.401) did not have a significant relationship with the incidence of ARI in toddlers. Conclusion: There is a significant relationship between the nutritional status of under-nourished toddlers and the low knowledge of toddler mothers and the incidence of ARI in toddlers at the Menteng District Health Center, Central Jakarta in 2017. It is recommended that medical staff on duty at the Menteng District Health Center be able to provide counseling to the public regarding the importance of paying attention to the nutritional status of toddlers, as well as providing education about ARI to the public, especially all mothers of children under five.